Cellular response to alkylating agent MNNG is impaired in STAT1‐deficients cells. Issue 10 (27th July 2016) - Ah‐Koon, Laurent; Lesage, Denis; Lemadre, Elodie; Souissi, Inès; Fagard, Remi; Varin‐Blank, Nadine; Fabre, Emmanuelle E.; Schischmanoff, Olivier
Abstract: The SN 1 alkylating agents activate the mismatch repair system leading to delayed G2 /M cell cycle arrest and DNA repair with subsequent survival or cell death. STAT1, an anti‐proliferative and pro‐apoptotic transcription factor is known to potentiate p53 and to affect DNA‐damage cellular response. We studied whether STAT1 may modulate cell fate following activation of the mismatch repair system upon exposure to the alkylating agent N ‐methyl‐ N ′‐nitro‐ N ‐nitrosoguanidine (MNNG). Using STAT1‐proficient or ‐deficient cell lines, we found that STAT1 is required for: ( i ) reduction in the extent of DNA lesions, ( ii ) rapid phosphorylation of T68‐CHK2 and of S15‐p53, ( iii ) progression through the G2 /M checkpoint and ( iv ) long‐term survival following treatment with MNNG. Presence of STAT1 is critical for the formation of a p53‐DNA complex comprising: STAT1, c‐Abl and MLH1 following exposure to MNNG. Importantly, presence of STAT1 allows recruitment of c‐Abl to p53‐DNA complex and links c‐Abl tyrosine kinase activity to MNNG‐toxicity. Thus, our data highlight the important modulatory role of STAT1 in the signalling pathway activated by the mismatch repair system. This ability of STAT1 to favour resistance to MNNG indicates the targeting of STAT1 pathway as a therapeutic option for enhancing the efficacy of SN1 alkylating agent‐based chemotherapy.